Numerical simulation of cavitating two-phase gas-liquid three-dimensional flow in a duct of varying cross-section based on homogenous mixture model - Duc, Nguyen The (Vietnam Journal of Mechanics, 2006)
The paper presents a numerical method to simulate two-phase turbulent cavitating flows in ducts of varying cross-section usually faced in engineering. The method is based on solution of two-phase Reynolds-averaged Navier-Stokes equations of two-phase mixture. The numerical method uses artificial compressibility algorithm extended to unsteady flows with dual-time technique. The discreted method employs an implicit, characteristic-based upwind differencing scheme in the curvilinear grid systems. Numerical simulation of an unsteady three-dimensional two-phase cavitating flow in a duct of varying cross-section with available experiment was performed. The unsteady important characteristics of the unsteady flow can be observed in results of numerical simulation. Comparison of predicted results with experimental data for time-averaged velocity and phase fraction are provided.